Inclusive EFL Instruction in Rural Nepal Using ICT: Stories of Basic-Level Teachers - Kandel, Rajan Kumar; Bist, Resham Bahadur (Tribhuvan University Journal, 2025)
This study aimed to explore the perceptions and experiences of basic-level English teachers (BLETs) regarding the use of information and communication technology (ICT) for students’ inclusion in EFL instruction in remote schools of Nepal. This study adopted a narrative inquiry approach to elicit the stories of four committed English teachers of remote schools in the Karnali Province, Nepal. The data were collected through interviews and classroom observations using semi structured interview guidelines and a classroom observation protocol. The study revealed that BLETs use ICT as a tool for maintaining students’ autonomous and inclusive participation in EFL classes. Their ICT tools integrated teaching created an equitable teaching and learning environment, even in resource-constrained settings. Additionally, findings indicated that the use of ICT in the English as a foreign language (EFL) classroom strengthened inclusivity related to personal, social, gender, ethnic, and (dis)ability variability of the learners in their classes. The study contributes to understanding ICT-supported inclusive practices in resource constrained EFL contexts.